2003
DOI: 10.1074/jbc.m306923200
|View full text |Cite
|
Sign up to set email alerts
|

APOE Genotype and an ApoE-mimetic Peptide Modify the Systemic and Central Nervous System Inflammatory Response

Abstract: Human apolipoprotein E is the major apolipoprotein expressed in the brain and exists as three isoforms, designated E2, E3, and E4. Although evidence suggests that apolipoprotein E plays an important role in modifying systemic and brain inflammatory responses, there is little data investigating apoE isoform-specific effects in vivo. In this study, we compared the inflammatory responses of targeted-replacement mice expressing the human APOE3 and APOE4 genes after intravenous administration of lipopolysaccharide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
279
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 340 publications
(301 citation statements)
references
References 29 publications
13
279
1
4
Order By: Relevance
“…We have previously demonstrated that larger peptides derived from the apoE receptor‐binding region (apoE133‐149) retain the neuroprotective and anti‐inflammatory properties8, 17, 30, 52, 53 of the apoE holoprotein. However, these peptides were limited by their relatively larger size, resulting in lower CNS penetration and higher cost of production.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that larger peptides derived from the apoE receptor‐binding region (apoE133‐149) retain the neuroprotective and anti‐inflammatory properties8, 17, 30, 52, 53 of the apoE holoprotein. However, these peptides were limited by their relatively larger size, resulting in lower CNS penetration and higher cost of production.…”
Section: Discussionmentioning
confidence: 99%
“…CREE inflammation and influences repair following injury with allele-specific effects. The APOE E4 allele is associated with less effective downregulation of inflammatory cytokines in the brain than the APOE E3 allele and contributes to an earlier age of onset of Alzheimer disease (Lynch et al, 2003). A large number of studies have explored whether APOE contributes to MS susceptibility or influences the disease course.…”
Section: Apoementioning
confidence: 99%
“…ApoE, in an isoform-specific fashion, regulates the time of onset and amount of Ah deposition via effects on Ah clearance and fibrillogenesis in APP transgenic mice (Bales et al, 1997;DeMattos et al, 2004;Fagan et al, 2002;Holtzman et al, 2000). In addition, it has been proposed that apoE may also influence AD and other central nervous system (CNS) disorders by influencing additional biological processes such as neural repair and inflammation (Buttini et al, 1999;Lynch et al, 2003;Teter, 2000). Understanding the nature of interactions between apoE and other molecules in the brain is likely to provide important insights into its normal function as well as its role in disease.…”
Section: Introductionmentioning
confidence: 99%